2017
DOI: 10.1097/spv.0000000000000364
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Concurrent Prolapse Surgery on Stress Urinary Incontinence Outcomes After TVTO

Abstract: Regardless of POP surgery type, patients demonstrate improvements in validated SUI outcomes through 2 years. Multivariate analysis suggests that there is little difference in SUI outcomes after TVT obturator system across several different POP repair types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…As there is a high co-occurrence of pelvic organ prolapse and urinary incontinence, some surgeons decide to perform concomitant procedures, with good results. A retrospective cohort analysis of 102 patients who underwent the TVT obturator system implantation in conjunction with a variety of POP repair surgeries revealed that, regardless of the POP operation type, patients demonstrated improvement in validated SUI outcomes during the following two years [7]. Chai et al demonstrated that concomitant surgery at the time of mid-urethral sling implantation (MUS) did not increase complication rates, and women receiving such model of treatment had a significantly lower risk of objective failure after MUS [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As there is a high co-occurrence of pelvic organ prolapse and urinary incontinence, some surgeons decide to perform concomitant procedures, with good results. A retrospective cohort analysis of 102 patients who underwent the TVT obturator system implantation in conjunction with a variety of POP repair surgeries revealed that, regardless of the POP operation type, patients demonstrated improvement in validated SUI outcomes during the following two years [7]. Chai et al demonstrated that concomitant surgery at the time of mid-urethral sling implantation (MUS) did not increase complication rates, and women receiving such model of treatment had a significantly lower risk of objective failure after MUS [15].…”
Section: Discussionmentioning
confidence: 99%
“…Women with POP and coexisting or occult SUI have the highest risk of postoperative SUI [7,16]; however, the predictive value of demonstrable SUI is limited and varies between studies [17,18]. According to some authors, the use of a vaginal pessary can help detect occult SUI and decide whether the insertion of a MUS should be done on top of the prolapse surgery [19], but in the opinion of others occult SUI detection rates depend on the technique applied and can significantly vary, from 6% with pessary prolapse reduction, to 16% with manual, to 30% when using a speculum [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The universal approach may reduce the incidence of postoperative SUI in both symptomatic and asymptomatic POP patients 27,28 . Moreover, both subjective and objective symptoms of incontinence and LUTS were reduced after the combined surgery 7 . Chai et al have demonstrated that combined surgery did not increase complication rates, and it decreased the risk of objective failure after MUS 29 .…”
Section: Sui Often Coexists With Popmentioning
confidence: 93%
“…In order to reduce the postoperative SUI, some surgeons have preferred performing an anti-incontinence procedure at the time of prolapse surgery. It has been demonstrated that the concomitant incontinence surgery reduces both subjective and objective symptoms of incontinence and LUTS 7 . However, such surgery may constitute overtreatment and cause serious adverse events, for example, bleeding, bladder perforation, urinary tract infection, long-term pain and erosion, and incomplete bladder voiding 4,8 .…”
Section: Introductionmentioning
confidence: 99%